Culminating Crises: Reflections and Learnings for Sustainable Development*. Issue 1 (March 2023) - Pawar, Manohar
This article aims to reflect on culminating crises by analysing the impact of the COVID-19 pandemic, natural disasters, wars and conflicts and political-economy and discuss how these crises have affected sustainable development efforts with a view to suggesting some strategies. Drawing mainly from the secondary data and the author's reflections, each of the four crises is analysed in terms of its negative and positive consequences. Then how these crises have affected sustainable development efforts, particularly the achievement of the sustainable development goals, is discussed. In the final section, seven strategies are suggested to culminate these crises.